2022
DOI: 10.3389/fpsyt.2022.831992
|View full text |Cite
|
Sign up to set email alerts
|

Relating Compulsivity and Impulsivity With Severity of Behavioral Addictions: A Dynamic Interpretation of Large-Scale Cross-Sectional Findings

Abstract: Background and AimImpulsivity and compulsivity are two key temperament traits involved in behavior regulation. The aim of this study was to test several existing theories in explaining the role of impulsivity and compulsivity in symptom severity in various behavioral addictions.MethodsData were collected from a (representative) general population sample (N = 2,710, mean age:39.8 years (SD:13.6), 51% woman), and from people who are at increased risk of having a behavioral addiction (N = 9,528 in total, mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 103 publications
1
9
0
Order By: Relevance
“…The NA results reported that withdrawal criterion ("Restless or irritable when attempting to cut down or stop gambling") had the highest centrality values, regardless of sex. This result confirms our initial hypothesis about withdrawal being closely related to the course and severity of the addictive process [31], and fits with previous literature that emphasised the relevance of withdrawal to the severity of the GD [17,18,[32][33][34]. This might indicate that the gambling addiction process could be driven by compulsive motives with the aim of avoiding the discomfort associated with not gambling (negative reinforcement) [27][28][29], and suggest that, if the patient reports withdrawal, they may be more likely to also present with other GD criteria and, following the definition of the DSM-5, present greater severity of the disorder.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The NA results reported that withdrawal criterion ("Restless or irritable when attempting to cut down or stop gambling") had the highest centrality values, regardless of sex. This result confirms our initial hypothesis about withdrawal being closely related to the course and severity of the addictive process [31], and fits with previous literature that emphasised the relevance of withdrawal to the severity of the GD [17,18,[32][33][34]. This might indicate that the gambling addiction process could be driven by compulsive motives with the aim of avoiding the discomfort associated with not gambling (negative reinforcement) [27][28][29], and suggest that, if the patient reports withdrawal, they may be more likely to also present with other GD criteria and, following the definition of the DSM-5, present greater severity of the disorder.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the GD criteria associated with the promotion of the addictive process through negative reinforcement, such as withdrawal, may be directly related to the course and severity of the addictive process [31]. Moreover, several studies suggested that withdrawal would be one of the symptoms most closely related to the severity of GD [17,18,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the network approach can generate hypotheses regarding symptoms that play important roles in the development or progression of mental disorders (Contreras et al, 2019 ; Fried et al, 2017 ). The assumption of causally related symptoms can complement theoretical models of addictive disorders, which describe the step-by-step and cyclical progression and maintenance of addictive behaviors (for review, see Demetrovics et al, 2022 ; Perales et al, 2020 ). For example, a problem gambler might first experience the symptom of impaired control over use which might subsequently lead to heightened preoccupation and tolerance to the gambling behavior, which can further contribute to the development of withdrawal symptoms in addition to problems in social functioning and financial status (Demetrovics et al, 2022 ; Perales et al, 2020 ; Rhemtulla et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on workaholism have found prevalences ranging from 1.5% (Demetrovics et al, 2022) to 44.9% (Azevedo and Mathias, 2017). The differences in reported prevalences are wide and in this subsection, we will present several studies that report varying rates of workaholism.…”
Section: The Prevalence Of Workaholismmentioning
confidence: 96%